Effects of Brief Mindfulness Instructions on Reactions to Body Image Stimuli Among Female Smokers: An Experimental Study - Adams, Claire E. (Oxford University Press, 2013)
INTRODUCTION: Recent research has shown that body image stimuli increase negative affect and smoking urges among female smokers. Mindfulness (paying attention to present-moment experience with an attitude of nonjudgmental acceptance) may be a useful technique to minimize the influence of body dissatisfaction on negative affect, smoking urges, and smoking behavior. METHODS: This study investigated whether mindfulness influences how female college smokers respond to a body image challenge. The study used a 2×2 factorial design with body image challenge (trying on a bathing suit vs. looking at a purse) crossed with instructions (mindfulness vs. silence). Female smokers (n = 64; M (age) = 20.03 [±1.77], 87.5% Caucasian) were randomly assigned to one of four conditions: Purse + Silence (n = 16), Body Image + Silence (n = 15), Purse + Mindfulness (n = 15), and Body Image + Mindfulness (n = 18).